PERCEIVED IMPACT OF THE YOUTH ENTERPRISE DEVELOPMENT FUND ON THE YOUTH TOWARDS THE ESTABLISHMENT OF SMALL SCALE RURAL ENTERPRISES IN TURBO DIVISION, UASIN-GISHU COUNTY, KENYA - Nyaura, Jasper E; Sutter, Paul. C; Rono, Phillip K (Journal of Humanity, 2017)
The inception of the Youth Enterprise Development Fund has seen the rise of youth groups in rural areas. This paper is thus aimed at understanding the impact of the fund towards the youth establishment of small scale enterprises in Turbo Division. A descriptive research design was used in this paper. Data was collected using focused group discussion and self-administered questionnaires thus they were administered to the selected youth groups found in selected parts of the Turbo Division. Purposive technique was used in the specific youth of aged bracket 18 year to 35 years. Further, purposive and stratified sampling techniques were used in targeted youth groups. The sample size used was 147 drawn from Turbo Division. The salient findings of the study are that indeed the youth joined the small scale enterprises to obtain benefits through collaborative efforts, to gain and obtain skills and experiences, obtaining start-up capital and finally due to the unemployment. Moreover, impact made by the fund on individual life included; promoting togetherness, promoting income and sustained livelihoods thus improved economic statues, and eventually enhanced skills and experience that led to acquiring of more skills by joining polytechnics. Furthermore the fund had enhanced group development and participation. It is recommended that there should be enhanced youth group sustainability towards proper utilization of the fund.